Para uma ideia de parataxis como teor-de-verdade: Adorno e Hölderlin - Dias, João Paulo Andrade (2018)
Aesthetic Theory’s Afterword tells the footpaths of Theodor Adorno’s important, posthumous and unfinished work. Through letters and reports, his editors reveal an author profoundly occupied with a formal overwork of its writing. As it seems, this process presents itself as an irrevocable exigency, imposed by his own thoughtέ Such a redraw finds explanation on the demand by idea’s content itself; it rekindles the so-called search for style on Adorno’s thoughtέ Although the work remained unfinished, border notes, letters and testimonies offer an orientation to pervade this issue: it tells about the preparation of a paratactic formal organization under a writing construction principle well favored by Hölderlin’s on his late poetic writingέ Paratactic principle would flag the possibility of totality’s reconstruction through partials complexes’ side-by-side organization, in a way that all of them should be disposed on the same level. It results on such a well-balanced idea’s exhibition mode, which should guarantee a sort of singularity and expressivity that Adorno’s works have never achieved. The reports left behind open up a very wide range of study, namely, analyses covering since totality’s idea overwork until Adorno’s appropriation of Hölderlinέ We adjusted this wide spread with our research time, deciding for an investigation on “Parataxisμ On Hölderlin’s late poetry”, Adorno’s discourse and essayέ On this text, we can follow parataxis’ idea formulation, whose rescue became our taskέ Notably, our purpose demands an investigation on some of Adono’s central conceptsμ “poeticize” (das Gedichtete), thingcontent (Sachgehalt), immanent law of formation (immanentes Gesetz des Gebildes), truthcontent (Wahrheitsgehalt). We dealt with Adorno’s debate against Heidegger, just as with his critique on philologyν with commentators’ support, we attentively analyzed Hölderlin’s poems and textsν finally, we followed all the steps of Adorno’s critical procedure, trying to detach all of the three layers of his work of art interpretation. Our parataxis’ idea rescue concludes that its formulation reflects and walks in through its inferior layers (thingcontent and immanent law of formation), but also surpasses them: in his Hölderlin analysis, Adorno draws out parataxis’ proper truthcontent